Clinical evaluation of the three-dimensional printed strut-type prosthesis combined with autograft reconstruction for giant cell tumor of the distal femur - Tan, Linyun; Li, Ye; Hu, Xin; Lu, Minxun; Zhang, Yuqi; Gan, Yuxiong; Tu, Chongqi; Min, Li (Frontiers in Oncology, 2023)
Propose This study aimed to describe the design and surgical techniques of a three-dimensional (3D) printed strut-type prosthesis with a porous titanium surface for distal femur giant cell tumors of bone (GCTB) and evaluate the short-term clinical outcomes. Methods From June 2018 to January 2021, 9 consecutive patients with grade I or II GCTB in the distal femur underwent extended intralesional curettage followed by 3D-printed strut-type prosthesis combined with autograft reconstruction were retrospectively reviewed to assess their clinical and radiographic outcomes. Results All patients were followed up for 30.8 ± 7.5 months (18–42 months) after surgery. The mean affected subchondral bone percentage and the mean subchondral bone thickness before surgery was 31.8% ± 9.6% (range, 18.2% 50.2%) and 2.2 ± 0.8 mm (range, 1.2-4.0 mm), respectively. At the final follow-up, all the patients were alive without local recurrence; no postoperative complications were observed. Patients had significant improvements in postoperative MSTS-93 score [(26.7 ± 2.4) vs. (18.8 ± 3.7), P < 0.05], and ROM [(122.8° ± 9.1°) vs. (108.3° ± 6.1°), P < 0.05] compared with their preoperative statuses. Furthermore, the mean subchondral bone thickness has increased to 10.9 ± 1.3 mm (range, 9.1-12.1 mm). Conclusion 3D-printed strut-type prosthesis combined with autograft reconstruction provides acceptable early functional and radiographic outcomes in patients with grade I or II GCTB in distal femur due to the advantages of the prosthesis such as good biocompatibility, osseointegration capacity, and subchondral bone protection. If our early outcomes can be further validated in studies with more patients and sufficient follow-up, this method may be evaluated as an alternative for the treatment of grade I or II GCTB in the distal femur.